À chacun sa biodiversité - Chantal Aspe; Didier Genin (Revue d'ethnoécologie)
Natural resources and territories management can take diverse forms, depending on ways of thinking and knowledge of people involved in. Based on examples taken from three contrasted areas (Regional Natural Parks of Luberon and Queyras in Southern France, and High Atlas territories in Morocco), we will show to which extent academic and local approaches differ in the ways of perceiving, managing and shaping territories, as well as biodiversity concerns. Territory delimitations and zoning illustrate these discrepancies: divisions of the total area on the basis of specific species or ecosystem protection problematic, or accordance with national or international directives in matter of environmental protection, on the one hand; geographic, historical, cultural and economical criterions, and a generalized concern of seeking functional complementarities of differentiated resources areas uses, on the other hand. Concerning biodiversity, the academic approach aims at defining general rules by optimizing researches and specialized knowledge on specific elements of biodiversity such as a species or an ecosystem, while locals argue forms of local particularisms, away from any generalization, but whose vision combines both systemic and functionalist aspects in relation to human activities. This usually leads to a certain foul’s dialogue between these actors, which is exacerbated by a strong power asymetry in matter of formal resource management competencies, and by a certain mutual ignorance concerning the content and the construction modes of these different types of knowledge.